Penicillin Allergy Testing Is Cost-Saving: An Economic Evaluation Study. (28th February 2020) - Sousa-Pinto, Bernardo; Blumenthal, Kimberly G; Macy, Eric; Pereira, Ana Margarida; Azevedo, Luís Filipe; Delgado, Luís; Fonseca, João Almeida
Abstract: Background: Having a penicillin allergy label is associated with the use of less appropriate and more expensive antibiotics and increased healthcare utilization. Penicillin allergy testing results in delabeling most allergy claimants and may be cost-saving. This study aimed to project whether penicillin allergy testing in patients reporting a penicillin allergy is cost-saving. Methods: In this economic evaluation study, we built decision models to project the economic impact of 2 strategies for a patient with a penicillin allergy label: (1) perform diagnostic testing (drug challenges, with or without skin tests); and (2) do not perform diagnostic testing. The health service perspective was adopted, considering costs with penicillin allergy tests, and with hospital bed-days/outpatient visits, antibiotic use, and diagnostic testing. Twenty-four base case decision models were built, accounting for differences in the diagnostic workup, setting (inpatient vs outpatient) and geographic region. Uncertainty was explored via probabilistic sensitivity analyses. Results: Penicillin allergy testing was cost-saving in all decision models built. For models assessing the performance of both skin tests and drug challenges, allergy testing resulted in average savings (in United States [US] dollars) of $657 for inpatients (US: $1444; Europe: $489) and $2746 for outpatients (US: $256; Europe: $6045). 75% of simulations obtained through probabilistic sensitivity analysis identified testing as the less costly option. Conclusions: Penicillin allergy testing was projected to be cost-saving across different scenarios. These results are devised to inform guidelines, supporting the adoption of policies promoting widespread testing of patients with a penicillin allergy label. Abstract : Penicillin allergy testing is projected to be cost-saving across different scenarios (including among inpatients and outpatients in the United States and Europe), economically supporting its generalized implementation across healthcare systems.